Inovasi Kepala Sekolah Dalam Meningkatkan Kualitas Guru Pendidikan Agama Islam Di Sekolah MAN 3 Jombang - Shalahuddin, Teguh; Sirojuddin, Didin (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
The principal is someone who leads a school institution where the role of the principal is very important in the progress and progress of education in the school. Principal innovation is a new thing or idea initiated by the principal which aims to advance the school with various new innovations. In learning, teachers are an important aspect for student development. In this case, schools play an important role in improving the quality of teachers by providing innovations aimed at improving the quality of teachers so that with these innovations the school principal can improve the quality of teachers to be better, which will enable progress and effectiveness in learning. In this research, researchers were able to find several innovations provided by school principals in improving the quality of PAI teachers, namely Class Control via Electronics and digital-based learning, from several of these innovations the principal succeeded in improving the quality of teachers. The results of this research can not only be used as a reference for further research, but can also be a motivation for readers to become innovative individuals. This research uses descriptive qualitative analysis methods. Researchers in collecting data use interviews, observation and documentation. The research which aims to collect this data was carried out in 2024. From the results of this research the researcher concluded that the school principal had made innovations to improve the quality of PAI teachers at MAN 3 Jombang and had succeeded in improving the quality of PAI teachers.